ETIKA PROFESI AKUNTANSI DALAM PERSPEKTIF ISLAM - Zulaika Matondang (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2015)
Professional ethics is intended to allow the workers perform their dutiesand responsibilities seriously , and do not perform fraud in its work . So itis an accountant who is always associated with the financial statements .For that reason , so that the accounting professional ethics can be done itneeds to make a code of conduct in the workplace . An accountant mustrecord all transactions that occur with reports in truth , in the view ofIslam accounting profession must possess honest , not fraud in any form.Allah ordered all the people to be honest in the work as contained in theverses of the Quran .